19th Century Malay manuscripts and royal Malay letters: identification of writing ink and its characteristics - Abdul Razak, Rajabi; Othman, Raihan (UMK Press, 2018)
The British Library holds over a hundred Malay composition writings and a few hundreds of Malay letters and reports, dated from the seventeenth to the nineteenth century. This research dedicated to examine the writing ink condition in 3 samples of Malay manuscripts and 12 samples of Royal Malay letters from the British Library collections. They were examined using multispectral imaging apparatus (non-destructive method) to inspect the physical conditions of the writings and also to identify the types of pigments/dyes used. The present work emphasizes on the black ink since it was predominantly used in writings of the early manuscripts. In most of the 19th century Malay manuscripts studied, the black ink writings are still in good conditions. The fact that these manuscripts survived until today proves the durability and permanency of the Malay traditional ink. Multispectral analysis, supported by infrared imaging, revealed that all but two manuscripts, even the Royal Malay letters, were written using carbon black ink that is most likely produced by the indigenous Malay recipe.